Effect of carbazochrome sodium sulfonate combined with tranexamic acid on blood loss and inflammatory response in patients undergoing total hip arthroplasty. Issue 6 (3rd June 2021) - Luo, Yue; Zhao, Xin; Yang, Zhouyuan; Yeersheng, Releken; Kang, Pengde
Abstract : Aims: The purpose of this study was to examine the efficacy and safety of carbazochrome sodium sulfonate (CSS) combined with tranexamic acid (TXA) on blood loss and inflammatory responses after primary total hip arthroplasty (THA), and to investigate the influence of different administration methods of CSS on perioperative blood loss during THA. Methods: This study is a randomized controlled trial involving 200 patients undergoing primary unilateral THA. A total of 200 patients treated with intravenous TXA were randomly assigned to group A (combined intravenous and topical CSS), group B (topical CSS), group C (intravenous CSS), or group D (placebo). Results: Mean total blood loss (TBL) in groups A (605.0 ml (SD 235.9)), B (790.9 ml (SD 280.7)), and C (844.8 ml (SD 248.1)) were lower than in group D (1, 064.9 ml (SD 318.3), p < 0.001). We also found that compared with group D, biomarker level of inflammation, transfusion rate, pain score, and hip range of motion at discharge in groups A, B, and C were significantly improved. There were no differences among the four groups in terms of intraoperative blood loss (IBL), intramuscular venous thrombosis (IMVT), and length of hospital stay (LOS). Conclusion: The combined application of CSS and TXA is more effective than TXA alone in reducing perioperative blood loss and transfusion rates, inflammatory response, and postoperative hip pain, results in better early hip flexion following THA, and did not increase the associated venous thromboembolism (VTE) events. Intravenous combined with topical injection of CSS was superior to intravenous or topical injection of CSS alone in reducing perioperative blood loss. Cite this article: Bone Joint Res  2021;10(6):354–362.